CHRONOTYPE AND ATHLETIC PERFORMANCE IN DIFFERENT TIME OF DAY - Das, Subal Chandra; Singh, Somanpreet; Chakraborty, Sangita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
For this study, total of 26 (13 male and 13 female) subjects were selected from the Department of Physical Education, Central University of Kashmir, age ranged between 23 to 27 years. Non-Probability sampling such as purposive sampling was used in the present study. In the present study chronotype was selected as the Independent Variable whereas Speed, Agility and Lower body explosive strength was considered as the dependent variables. Chronotype is understood to reflect a spectrum of behaviors ranging from an extreme preference for morning activity to an extreme preference for evening activity. Horneostberg, (1976) morning - evening question was used to find out the chronotype of the athletes. All the tests were conducted and administered at different times in a day. i.e., morning from 9.30 AM to 10:30 AM and evening between 03:00 pm to 04:00 pm. The obtained data was analyzed by applying the descriptive statistics and paired “t” were worked out and the results have been presented in different tables. . Therefore, it was concluded that mean differences in the explosive strength and agility in morning and evening was statistically significant and it was also concluded that mean differences in the morning 50m sprint and evening 50m sprint were not statistically significant.